Smart Processing Machines and Business Efficiency in Goat Milk Agro-Enterprises - Achmad Tavip Junaedi; Harry Patuan Panjaitan; Nicholas Renaldo; Nyoto Nyoto; Jahrizal Jahrizal; M Dalil; Jaswar Koto; Sulaiman Musa; Nabila Wahid; Kristy Veronica; Umar Faruq (Luxury: Landscape of Business Administration, 2025)
The increasing demand for functional and health-oriented dairy products has positioned goat milk agro-enterprises as a promising business sector, particularly in emerging economies. Despite this potential, many goat milk businesses face persistent challenges related to production inefficiency, high operational costs, and limited scalability. This study aims to examine the impact of smart processing machines on business efficiency in goat milk agro-enterprises. Using a quantitative approach, data were collected from small and medium-sized goat milk processing enterprises and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that smart processing machine adoption has a positive and significant effect on business efficiency, including cost efficiency, productivity, and operational effectiveness. The findings indicate that smart processing machines function not merely as technological tools but as strategic business resources that enhance operational performance and competitiveness. This study contributes to the business and agribusiness literature by providing empirical evidence at the production-machine level and highlighting the strategic value of smart manufacturing technologies in small-scale agro-enterprises. The findings offer practical insights for business owners, policymakers, and technology developers in promoting sustainable and efficient goat milk processing businesses.